Whether Obesity Needs to be Addressed in Pre-Pregnancy Advice? (Journal of Bangladesh College of Physicians and Surgeons, 2010)
Objective: When obesity need to be addressed, during pre pregnancy obesity is common and it adversely affects the maternal and perinatal outcomes. Maternal obesity has major impact on health service, specially on in relation to the level of care required, the cost and resources implications, complications and risk to the mothers and infant. Methods and Materials: It was the prospective study 500 pregnant women ( 250 were obese and 250 were normal), The period of 3 years from January 2004 to December 2008. All the events during antenatal, during delivery and postnatal were recorded, and compare the outcomes. Result: We found pre-eclampsia ( 10 for obese and 2 for normal, p = 0.01), Positive OGTT 100 for obese and 8 for normal P = 5.72, PPH 25 for obese and 5 for non obese P = 0.00021, wound infection 5 for obese and one in non obese group p = 0.0003, others like UTI, we got 60 for obese and 15 for non obese P = 1.7401. Pueperial sepsis 3 in obese and 1 for non obese p=0.3131. Pre eclapsia, PPH and wound infection shows significantly high in obese group. Similarly NICU admission, macrosomia and fetal distress were more in obese pregnant than non obese women. So pregnancy among obese women should classified as high risk pregnancy. From the study we concluded that weight reduction before pregnancy need to be discussed as pre-pregnancy counseling. Key words: obesity; pre-pregnancy; counselling DOI:10.3329/jbcps.v27i3.4291 J Bangladesh Coll Phys Surg 2009; 27: 144-147